2019
DOI: 10.1016/j.intfin.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The Brexit vote and currency markets

Abstract: This paper studies the effect of the Brexit vote on the intraday correlation and volatility transmission among major currencies. We find that the vote causes an increase in the correlation among the safe-haven currencies of the Swiss franc and Japanese yen as well as gold, and also find a decrease in their correlation with the directly involved currencies of British sterling and the Euro. These changes are due to the appreciation of the former group and the depreciation of the latter group which represents a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Recent developments, such as BREXIT and financial crises, that promote uncertainty or even distrust in the conventional monetary or sovereign systems require more examinations of these cryptocurrencies. For example, Dao et al ( 2019 ) showed that BREXIT is associated with an increase in the correlations among safe-haven currencies (CHF and JPY) and a decrease in the correlation between GBP and EUR, which were directly involved in the BREXIT decision. For the latter two currencies, they also found a significant decrease of 64% in the transmission of volatility between GBP and EUR after the BREXIT decision.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments, such as BREXIT and financial crises, that promote uncertainty or even distrust in the conventional monetary or sovereign systems require more examinations of these cryptocurrencies. For example, Dao et al ( 2019 ) showed that BREXIT is associated with an increase in the correlations among safe-haven currencies (CHF and JPY) and a decrease in the correlation between GBP and EUR, which were directly involved in the BREXIT decision. For the latter two currencies, they also found a significant decrease of 64% in the transmission of volatility between GBP and EUR after the BREXIT decision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our study contributes to several evolving strands in the literature. First, we add to the studies dealing with the role of traditional safe-haven currencies in the framework of diversification and risk reduction under market stress (e.g., Fatum and Yamamoto 2016 ; Dao et al 2019 ; Urquhart and Zhang 2019 ). We analyze the connectedness of the commonly used safe-haven currencies with all the components of the sovereign yield curve and the most dominant cryptocurrency, Bitcoin.…”
Section: Introductionmentioning
confidence: 99%
“…Brexit has been analysed from a wide range of angles including identifying reasons for the results of the referendum (Alabrese et al 2019;Arnorsson and Zoega 2018;Goodwin and Heath 2017); understanding how uncertainty associated with the Brexit referendum result may affect firms and industries (Hill et al 2019); the effect of Brexit on EU and UK stock markets and exchange rates (Bashir et al 2019;Dao et al 2019;Guedes et al 2019;Shahzad et al 2019); the effects of Brexit on trade (Dhingra et al 2017); the effects of Brexit on specific industries such as agriculture and seafood (Symes and Phillipson 2019); the potential impact of Brexit on the Pelagic Advisory Council to secure a long-term sustainable pelagic fisheries management (Ohms and Raakjaer 2019); and how Brexit may affect the health services in the UK (Fahy et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of regulatory instruments is significantly influenced by the degree of liberalization of foreign exchange markets, which causes the effects after the opening of local markets, the effects of major markets and market closures [11]. These effects are related to the transfer of volatility between currencies, which clearly demonstrates the situation with Brexit [12].…”
Section: Methodsmentioning
confidence: 99%